Influence of CSR Practices and Ethical Leadership on Consumer Trust: Mediating Roles of Brand Image and Perceived Sustainability - Santhosh Kumar , K (SAIM Journal of Social Science and Technology, 2025)
Purpose: This research examines the influence of Corporate Social Responsibility (CSR) practices and Ethical Leadership on Brand Image, and how these factors subsequently affect Perceived Sustainability, ultimately fostering Consumer Trust. Research Methodology: A quantitative research design was utilized, collecting data from 150 respondents spanning diverse demographic groups. Statistical analyses including descriptive statistics, reliability testing, and factor analysis were conducted to ensure construct validity and internal consistency. Findings: Results demonstrate a significant positive relationship between CSR and Ethical Leadership on Brand Image. This enhanced Brand Image further strengthens Perceived Sustainability perceptions, which in turn cultivates higher levels of Consumer Trust. Conclusion: The study highlights the critical role of ethical leadership and socially responsible initiatives in shaping favorable brand perceptions and promoting sustainable business practices that build enduring consumer trust. Originality: This research contributes to the literature by empirically linking CSR and Ethical Leadership with Brand Image and Perceived Sustainability, advancing understanding of their combined effect on Consumer Trust. It provides actionable insights for organizations aiming to reinforce trust and sustainability through ethical and responsible practices.